Key performance indicators to assess and reverse the negative impacts of SECA policies for Ro-Ro Shipping - Zis, Thalis; Psaraftis, Harilaos N. (My University, 2018)
The 0.1% sulphur limit within Sulphur Emission Control Areas (SECA) has made compulsory the use of either pricier ultra-low sulphur fuel, or the installation of abatement technologies that require significant capital investments. Due to the unexpectedly low fuel prices, Ro-Ro operators have been able to cope with the new sulphur limits, but recent research has shown that if fuel prices increase some Ro-Ro services may face the risk of closure. This paper proposes three key performance indicators (KPIs) to enable the asssessment of the impact of SECAs on Ro-Ro shipping. The KPIs are used on a set of case studies for services of a leading European Ro-Ro operator, and allow benchmarking of a series of operational and policy measures that aim to reverse the negative impacts of SECAs. The operational measures consider speed reduction, new sailing frequency, fleet reconfiguration, as well as investments in abatement technologies. Policy measures include the options of either subsidizing shippers or ship operators, or alternatively introducing new taxes on landbased options. The KPIs can be useful to ship operators seeking to improve the resilience of their network, as well as to regulatory bodies designing new environmental policies and understanding any negative implications these may have on ship operators.
Keywords: Green Logistics, Modal shifts, Ro-Ro shipping